Identifying perceptions and knowledge gaps among pre-clinical and clinical medical students regarding placebo therapy - Haseeba Mukhtar; Syeda Unzila; Taskeen Baber; Syeda Mahdokht Shah; Sujjad Khan; Sidra Khan (International Journal of Pathology, 2024)
Background: Misleading definitions and perceptions of placebo and placebo effect result in fewer realizations on the subject, hence reducing its perceived importance and applications. This study aims to assess undergraduate medical students’ perceptions and knowledge gaps regarding placebo therapy across different stages of their education. Methods: A comparative cross-sectional study was conducted for six months, from December 2022 to May 2023, among 350 pre-clinical students (1st and 2nd year MBBS) and 526 clinical students (3rd, 4th, and Final-year MBBS) to assess their perceptions regarding placebo and placebo effect through a validated questionnaire. SPSS was used for analyses, and Pearson’s Chi-square was applied, keeping the statistically significant value of <0.05. Results: The study included 876 medical students, with 350 pre-clinical and 526 clinical participants. The mean age was 21.32 years (±1.606). A significant gender distribution was observed, with 45.5% males and 54.5% females. Clinical students demonstrated a greater acceptance of placebo use (68.3% vs. 62.3%, p=0.031) and were more likely to find placebo therapy ethical in psychological cases (70.3% vs. 60.3%, p=0.006). Knowledge assessment revealed that 65% had fair knowledge of placebo therapy, 31.8% had good knowledge, while only 3.2% were highly knowledgeable. Conclusion: The study revealed that many pre-clinical and clinical students held misconceptions about placebo therapy, believing it permissible and beneficial in treating organic disorders. This highlights a significant knowledge gap, emphasizing the need for improved education on placebo use and ethics.